Alcohol as a risk factor for drug-induced diseases - Sychev, D. A.; Ostroumova, O. D.; Pereverzev, A. P.; Kochetkov, A. I.; Ostroumova, T. M.; Ebzeeva, E. Yu; Klepikova, M. V. (Kachestvennai͡a︡ klinicheskai͡a︡ praktika, 2021)
Administration of a rational and safe drug therapy is one of the most challenging issues for healthcare professionals. The frequency of hospitalizations due to the adverse drug reactions in the years 2000 — 2015 was estimated at 6.3 (3.3—11.0 %) for developed countries and 5.5 % (1.1—16.9 %) for developing countries. It is known that alcohol intake is a risk factor for many socially significant diseases, including arterial hypertension, coronary heart disease, chronic heart failure, etc., however, many doctors pay insufficient attention to the fact that many drugs, for example, beta-blockers, antidepressants, bezodisepines, calcium antagonists, can interact with alcohol when consumed simultaneously and, thus, increase the risks of adverse drug reactions. There are 2 main types of interactions between alcohol and drugs: pharmacokinetic (at the stage of absorption, distribution, metabolism and elimination) and pharmacodynamic (at the stage of effects and receptors). For example: the simultaneous intake of alcohol and paracetamol leads to the formation of toxic metabolites due to the induction of cytochrome P450 isoenzymes by alcohol. Another example is decrease in presystemic elimination and stimulation of the metabolism of tricyclic antidepressants; an increase in the elimination of imipramine and desipramine in patients with chronic alcoholism after detoxification therapy, and so on. In this article, the authors analyzed and systematized data from open literature sources in order to inform health care professionals about the possible risks associated with the interaction of alcohol and drugs and various pharmacological groups.